A importância do ponto de venda na influência dos consumidores da geração Z na compra de produtos de tecnologia - Coelho, Daniela Andrade Figueira Pinto (2013)
Given this cyber revolution formed by a discharge of digital content and different formats of media and advertising, generation Z emerges, breaking the traditional model of consumption to a more interactive and dynamic whose main vectors are formed by connectivity and sharing experience. On the other hand, the retailers are remaining with the traditional model bringing a limited and offline experienre, promoting a dichotomy between the potential consumers seeking an exclusive and fun experience. The following study seeks to understand the qualities, features and aspirations of this new consumer experience at the point of sale in order to present the main challenges and changes needed to attract this demanding consumer member of Generation Z. The study includes a survey at the point of sale and interviews to understand how this generation realizes the point of sale. The research reveals that these children are seeking a more interactive and dynamic environment at the point of sale and the retail must change to attend this new generation